The Role of Human Resource Management in Organizations - Alisia Pingky Saputri; Heldy Ramadhan Putra Pembangunan; Yogy Hafidz Adiyatma; Nantri Kusuma Fii Ilayana; Alfiansyah Daffa Prasetya (LPPM STIAB Jinarakkhita Lampung, 2023)
The role of human resource management in organizations in the Kartasura sub-district has been well designed and implemented in accordance with the needs of the region and the residents of Kartasura. The purpose of this research is to find out how the role of human resource management in the Kartasura sub-district is carried out. This research was conducted using qualitative methods such as observation, interviews, and literature review studies. The role of human resource management itself is divided into three. First, in administration, the Kartasura sub-district is responsible for carrying out the work program activities that have been designed. Second, operational and advocacy roles are carried out to control employees so that they can contribute well so that the work carried out can run effectively and efficiently. Third is the strategic role of human resources that must be carried out to support the work program that will be carried out. With the existence of a strategy in the work program that will be carried out, it is hoped that it can provide results that are in accordance with the goals desired by the company or organization.